RADIATIVE TRITIUM CAPTURE ON 3He AT LOW AND ASTROPHYSICAL ENERGIES - Dzhazairov-Kakhramanov, A.V.; Karipbayeva, L.T.; Steblyakova, A.A. (Academic Scientific Journal of Computer Science, 2020)
The radiative tritium capture on 3He at low and astrophysical energies was considered in the framework of the modified potential cluster model. It is shown that on the basis of potentials coincided with scattering phase shifts and the energy of bound state it is possible to correctly represent available experimental data. The two-cluster potential model described in this paper, used intercluster forces with forbidden states, in many cases, allow one correctly to describe some nuclear characteristics for different light and lightest nuclei, and, evidently do not yet exhaust completely their potential. The more especially as reported here methods and results are applicable to certain problems of nuclear astrophysics, concerned to light atomic nuclei and ultralow energies of interacting particles. In other words, these results have direct relationship to thermonuclear processes flowing in the Sun, stars, some other objects of our Universe and Universe in whole, at different stages of its forming and developing. It is possible to use one channel cluster model, which, in more cases, is a good approach to the real existent situation. Such model allows relatively easy to carry out any calculations of nuclear characteristics in scattering processes and bound states, even in that systems, where solving methods of many-body problem either very cumbersome in numerical implementation or do not lead to the concrete quantitative results at all.